Exploring Interactivity of ABS-CBN - Aguila, Almond Pilar N. (Plaridel Journal of Communication, Media, and Society, 2007)
ABS-CBN Interactive, the youngest subsidiary of media giant ABS-CBN, was one of the first Philippine companies to ride on the wave of the Internet boom in 2000. Although this growing industry experienced a traumatic blow with a universal dotcom bust in the early years of the new millennium, the World Wide Web is slowly but surely becoming a lucrative enterprise. Managing Director Paolo Pineda shares his insights on the successes, failures, and challenges of this exciting field of communication. The Interactive Group has capitalized on the technology’s potential to bring together traditional and new media. Its services include interactive TV and movie promotions, news, celebrity information, value-added services for mobile phones (ringtones, ringback tones, logos, picture messages, etc.), and online games. This interview offers a different view of how new media is enhancing the use of traditional media in the Philippines.